Peran Guru Ngaji sebagai Komunikator Dakwah dalam Pembentukan Religiusitas Santri di Masjid Baitul Karim Purwokerto - Adila Ivana Lalita; Ega Putri Hapsari (CV Omah Kreator, 2025)
This study aims to analyze the role of guru ngaji (Qur’an teachers) as da’wah communicators in shaping the religiosity of students at Baitul Karim Mosque, Sawangan Village, Purwokerto. The research focuses on how da’wah communication is carried out through Qur’anic learning activities in non-formal Islamic education (TPQ) and how these interactions influence the internalization of religious values among students. This research employed a qualitative descriptive method with data collected through in-depth interviews and participatory observation. The findings indicate that guru ngaji serve not only as Qur’an instructors but also as da’wah communicators who instill akhlaqul karimah values through exemplary behavior, persuasive communication, and habituation of daily worship. Consistent interpersonal communication by teachers was found to be effective in enhancing students’ religious awareness and behavior. The novelty of this study lies in emphasizing the perspective of da’wah communication within mosque-based non-formal education, a topic that has received limited academic attention.